2009
DOI: 10.1245/s10434-009-0326-7
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Limb Infusion as Palliative Treatment for Advanced Limb Disease in Patients with AJCC Stage IV Melanoma

Abstract: Minimally invasive ILI can effectively be used as palliative treatment to provide local tumor control and limb salvage in stage IV melanoma patients with advanced, symptomatic limb disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…No excessive toxicity or morbidity was seen in MIA patients, despite the fact that their average age was considerably higher than that of patients in most ILP studies 41, 61. Even in patients who suffer from distant metastatic disease and have concurrent symptomatic limb disease, ILI can effectively be used as a palliative treatment to provide local limb tumor control and limb salvage 62. Also, because there is hardly any groin scar tissue following ILI, the procedure can easily be repeated if there is disease recurrence.…”
Section: Discussionmentioning
confidence: 97%
“…No excessive toxicity or morbidity was seen in MIA patients, despite the fact that their average age was considerably higher than that of patients in most ILP studies 41, 61. Even in patients who suffer from distant metastatic disease and have concurrent symptomatic limb disease, ILI can effectively be used as a palliative treatment to provide local limb tumor control and limb salvage 62. Also, because there is hardly any groin scar tissue following ILI, the procedure can easily be repeated if there is disease recurrence.…”
Section: Discussionmentioning
confidence: 97%
“…No increase in toxicity or morbidity was seen in the MIA patients, despite the fact that their average age was considerably higher than those seen in most ILP studies [17, 37]. Even in patients who suffer from distant metastatic disease and concurrent symptomatic limb disease ILI can effectively be used as a palliative treatment to provide local tumor control and limb salvage [38]. Also, because scar tissue is hardly formed following ILI, the procedure can easily be repeated in case of recurrent disease.…”
Section: Discussionmentioning
confidence: 99%
“…ILI may also be performed in patients who also have distant metastatic disease in a palliative effort to control symptomatic locoregional disease. Kroon et al reported a limb salvage rate of 86% in a series of 37 patients with symptomatic limb disease and documented distant metastases at the time of ILI (Kroon et al 2009a). While predominately performed for cutaneous melanoma, ILI has also been used to treat locallyadvanced soft tissue sarcoma and non-melanoma cutaneous malignancies including Merkel cell carcinoma, and squamous cell carcinoma Turaga et al 2011;O'Donoghue et al 2017).…”
Section: Patient Selection and Indicationsmentioning
confidence: 99%